Ohmic and Diamagnetic Currents Contribution on the Electromagnetic Penetration Depth of a Conducting Surface - Adam Badra Cahaya (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
Due to its conducting electron, metal is a good reflector for electromagnetic wave. An electromagnetic wave penetrating a metallic surface has a finite penetrating depth. There are two limit that are well studied in the physics textbooks. They are high frequency electromagnetic wave penetrating a metal with small conductivity and a static (low frequency) field penetrating a superconductor (metal with infinitely large conductivity). In this article we study the intermediate regime between these two limits. By setting the electric current density as the total sum of both Ohmic and Diamagnetic currents, we derive the penetration depth in the intermediate regime., we show the transition between these two limits.